Identification of a bio-signature for barley resistance against Pyrenophora teres infection based on physiological, molecular and sensor-based phenotyping. (December 2021) - Pandey, Chandana; Großkinsky, Dominik K.; Westergaard, Jesper Cairo; Jørgensen, Hans J.L.; Svensgaard, Jesper; Christensen, Svend; Schulz, Alexander; Roitsch, Thomas
Graphical abstract: Highlights: Phenomics approach to assess infection of four barley genotypes by P. teres . Identification of an enzyme activity fingerprint for resistance against P. teres . Distinct temporal dynamics of gene expression profiles reflect pathogen resistance. Resistance correlates with a specific reflectance and fluorescence signature. Pre-symptomatic detection of pathogen infection by sensor-based imaging. Abstract: Necrotic and chlorotic symptoms induced during Pyrenophora teres infection in barley leaves indicate a compatible interaction that allows the hemi-biotrophic fungus Pyrenophora teres to colonise the host. However, it is unexplored how this fungus affects the physiological responses of resistant and susceptible cultivars during infection. To assess the degree of resistance in four different cultivars, we quantified visible symptoms and fungal DNA and performed expression analyses of genes involved in plant defence and ROS scavenging. To obtain insight into the interaction between fungus and host, we determined the activity of 19 key enzymes of carbohydrate and antioxidant metabolism. The pathogen impact was also phenotyped non-invasively by sensor-based multireflectance and –fluorescence imaging. Symptoms, regulation of stress-related genes and pathogen DNA content distinguished the cultivar Guld as being resistant. Severity of net blotch symptoms was also strongly correlated with the dynamics of enzyme activities already within the first day of infection. In contrast to the resistant cultivar, the three susceptible cultivars showed a higher reflectance over seven spectral bands and higher fluorescence intensities at specific excitation wavelengths. The combination of semi high-throughput physiological and molecular analyses with non-invasive phenotyping enabled the identification of bio-signatures that discriminates the resistant from susceptible cultivars.